Zmienność cech wiązu górskiego Ulmus glabra Huds. rosnącego na uprawie zachowawczej ex situ w Nadleśnictwie Oleszyce - Banach, Jacek; Puk, Izabela; Skrzyszewska, Kinga (Leśne Prace Badawcze, 2021)
The aim of this work was to investigate the variability of different features in wych elm Ulmus glabra Huds. Populations growing in the conservative plantation in the Kolonia Forest Subdistrict (Oleszyce Forest District). We examined the survival rate, height, and spring flushing of the elm trees as well as the occurrence of two leaf morphotypes after ten years since the establishment of the plantation. Statistically significant differences were found between the studied populations in terms of survival and height growth, while no difference was observed for spring flushing, which may be due to the close proximity in which the tested populations grow. The highest rate of survival was observed in the Bircza 33a population (87.3%), whereas the Lutowiska 40b population grew tallest (344.3 cm). Elms with leaves typical of the U. glabra ssp. montana (morphotype A – 84%) dominated the stand, while elms with leaves characteristic for the U. glabra ssp. glabra (morphotype B) were a minority with only 4%. However, within the Lutowiska 137g population, the share of morphotype B was as high as 25%.